Influência antrópica na qualidade dos aquíferos freáticos da sub-bacia do rio Monjolinho - Arruda, Natália de Souza (Universidade Federal de São Carlos, 2020)
The pressure of human activities in water sources results in changes in the environmental quality of river basins. Groundwater aquifers are important reservoirs and feeders for surface water sources. The analysis of rapidly changing geoenvironmental indicators helps to interpret anthropic interference in the quality of groundwater. For the effective management of water sources, it is necessary to study the environmental quality and the possible environmental impacts in strategic regions in the hydrographic basins. The purpose of this work was to investigate possible anthropic interference in the hydrochemical quality of groundwater aquifers in the Monjolinho river basin, upstream of Espraiado water abstraction in the municipality of São Carlos-SP. This section of the basin is inserted in a Protection and Recovery Area of Springs, in a peri-urban region, with high real estate pressure for the expansion of the urban perimeter. Through the detailing of land use and occupation, within the rural and urban areas, paying attention to potentially polluting activities, 28 physical-chemical parameters were chosen, sampled in 7 water tables, in the period of high and low precipitation. From the interpretation of the analysis, it can be noted that the aquifer aquifers Coluvionar and Itaqueri have different hydrochemistry, the aquifer being colluvial with a tendency to more acidic waters and the absence of some metals. Anthropic interference in hydrochemical quality was observed in wells P12, P13, P16, P19, P26 and P41. Well P26 showed high concentrations of N-nitrate. The study identified interference from urban and rural human activities, such as leakage of sanitary sewage and fertilizers in groundwater aquifers in the Monjolinho River sub-basin.
Anthropic influence on shallow groundwater quality in the Monjolinho sub-basin
Keywords: Qualidade da água subterrânea; Aquíferos rasos; Zona periurbana; Contaminação; Groundwater quality; Shallow aquifers; Periurban area; Contamination; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS; ENGENHARIAS::ENGENHARIA CIVIL::GEOTECNICA; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOLOGIA::GEOLOGIA AMBIENTAL; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOLOGIA::HIDROGEOLOGIA